2011
DOI: 10.1088/0031-9155/56/22/014
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of spatial priors on the performance of model-based IVUS elastography

Abstract: This paper describes methods that provide pre-requisite information for computing circumferential stress in modulus elastograms recovered from vascular tissue—information that could help cardiologists detect life-threatening plaques and predict their propensity to rupture. The modulus recovery process is an ill-posed problem; therefore additional information is needed to provide useful elastograms. In this work, prior geometrical information was used to impose hard or soft constraints on the reconstruction pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 63 publications
4
47
0
Order By: Relevance
“…25,26 However, in vascular imaging, additional constraints (i.e., geometric) are required to produce stable modulus elastograms. [32][33][34][35] Geometrically constrained inversion methods can tolerate higher noticeable amounts of measurement noise than those with just smoothness constraints. 33,35 We performed a pair-wise Welch's t-test on the results reported in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…25,26 However, in vascular imaging, additional constraints (i.e., geometric) are required to produce stable modulus elastograms. [32][33][34][35] Geometrically constrained inversion methods can tolerate higher noticeable amounts of measurement noise than those with just smoothness constraints. 33,35 We performed a pair-wise Welch's t-test on the results reported in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35] Geometrically constrained inversion methods can tolerate higher noticeable amounts of measurement noise than those with just smoothness constraints. 33,35 We performed a pair-wise Welch's t-test on the results reported in Fig. 7, which revealed that the modulus elastograms reconstructed with the three imaging methods were not significantly different (p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations